PENGARUH KEBIJAKAN PERTAHANAN DAN KEAMANAN UNI EROPA TERHADAP EKSISTENSI NATO DI KAWASAN EROPA - , Rosnani, Drs. Muhadi Sugiono, MA. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research explains about The Effects of European Unionâs Defense and Security Policy toward NATOâs Existence in European Region. It analyses the implications of Common Foreign and Security Policy as a policy in European Unionâs security and defense aspects. This research discovers that CFSP forming by European Union countries and the efforts in making CFSP effective have brought indirect effect toward NATOâs existence in European region. As a defense pact organization in European region, NATO has become a shelter for security for its country members, especially for those in European region in the era of Cold War. However, geopolitical changes that happened during post Cold War have raised European Union countriesâ consciousness for the needs of an independent institution in dealing with their territoriesâ security. Finally, NATOâs prospect in European region after the forming of CFSP, will be much depended on how strong European countriesâ effort in establishing a more capable CFSP institution and in making use of NATOâs assets into maximum in the execution of defense and security aspect.